The cytotoxic effects of different polycyclic aromatic hydrocarbons on the antioxidant function of the cultivated hepatocytes from Acanthopagrus arabicus: a comparative study Insert Title here (Development Engineering Conferences Center Articles Database, 2024)
The present study aimed to compare the toxicity of different polycyclic aromatic hydrocarbons, including naphthalene, phenanthrene, pyrene, and benzo(a)pyrene (B(a)P), on viability and the antioxidant function of cultivated hepatocytes from Arabian sea bream (Acanthopagrus arabicus) in vitro. Cultivated hepatocytes from A. arabicus were exposed to different but equal concentrations of four pollutants, including 0 (control), 10-2, 10-1, 1, 10, 102 and 103 μg/ml (in 0.01% DMSO) for 48 h. The results showed that the sensitivity of cultivated hepatocytes to all four pollutants increased in a dose-dependent manner; although, the toxicity of low concentrations of all four pollutants did not show a significant difference with the control cells. Cultured hepatocytes exposed to the highest concentrations of all studied pollutants showed the lowest levels of total antioxidant capacity (TAC) and glutathione content (GSH) and the highest levels of lipid peroxidation (LPO) and alanine transaminase (ALT) activity after 48 h. Naphthalene and B(a)P showed the highest and lowest toxicity, respectively. The level of cytotoxicity, cell viability and the level of antioxidant enzymes as well as liver damage indicator enzymes in the present study were mainly affected by naphthalene followed by phenanthrene, and pyrene and B(a)P had less effect. In conclusion, although all PAHs are able to suppress the antioxidant defense system, PAH compounds with lower molecular weight and fewer benzene rings have a more potential to inhibit antioxidants and increase the level of lipid peroxidation due to their more ability to pass through cell membranes.